Handbook of occupational safety and health - DiBerardinis, Louis J. (New York : John Wiley & Sons, 1999)
Introduction. Safety evaluations. Health evaluations. Control practices. Physical hazards and special topics. Legal affairs.
Keywords: Industrial hygiene; Industrial safety; Industrial hygiene -- Handbooks, manuals, etc; Industrial safety -- Handbooks, manuals, etc